THE USE OF INTERACTIVE SULS IN TEACHING THE TOPIC OF THE BIRD CLASS (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2025)
This article examines the application of interactive teaching methods for the topic “The Class of Birds” in biology education. It explores the effectiveness of methods such as group discussions, multimedia presentations, virtual simulations, and hands-on activities in enhancing students’ understanding and interest in ornithology. The study emphasizes the pedagogical shift from passive to active learning and demonstrates how interactive tools improve engagement and academic performance among middle school students.